Building Awareness and Action on Separated Waste Management For Students At SMA DM Triguna Padang - Rahmi Kurniati; Hayyu Yumna; Ithvi Marhamah; Rahmawati Darussyamsu (Pelita Eksakta, 2026)
DM Triguna High School is a private high school in Padang City. Several problems exist, including low student awareness of waste sorting and the lack of separate trash bins. The solution is to conduct education to increase awareness and action on separate waste processing. This activity aims to increase student awareness about the need for separate waste management and how to process it. Additionally, the school is equipped with separate trash bins to promote environmental awareness among students. The results obtained from this Community Service activity are data on the knowledge of community service participants before and after the training. There was an increase from an average score of 63.11 before education to 77.55 after schooling was provided. This indicates a growth of 22.87%. This data illustrates that community service activities have a positive impact on the knowledge of student participants and have an impact on partners.